Analisis persiapan guru dalam pembelajaran media manipulatif matematika di sekolah dasar - Syarifah Farhana; Aam Amaliyah; Agustini Safitri; Rika Anggraeni (ARKA INSTITUTE, 2022)
This study aims to find out how mathematics teachers view the manipulative materials method. This research was conducted using qualitative, descriptive methods and using a naturalistic qualitative approach. The data were collected through observation, interviews and documentation. The subject was the teacher. The results of the study indicate that the teacher's view of the use of manipulative materials methods can improve student learning outcomes in understanding mathematical concepts and procedures. Thus learning mathematics using the manipulative material method needs to be applied as a good learning, which can activate students and increase the ability of students to understand concepts.